QUALITY OF WORKING LIFE FACTORS HAPPY AT WORK AFFECTING ORGANIZATIONAL ENGAGEMENT OF ABC COMPANY EMPLOYEES - Yuprom, Apitta; Phongsamran, Suthum; Tanphan, Ingorn (Journal of MCU Nakhondhat, 2025)
The Objective of this Study: 1) To examine the quality of working life, happiness at work and organizational engagement of the ABC company’s employees. 2) To compare organizational engagement of the ABC company employees categorized by personal information 3) To investigate how quality of working life influences the organizational engagement of the ABC company employees. 4) To investigate how the employees are happy at work, the influences and organizational engagement at the ABC company. This is quantitative research. The sample population consisted of 114 ABC company employees. Questionnaires were utilized to collect the data. The statistical methods used for data analysis include frequency, percentage, mean, Standard deviation, t-test, F-test (One-way ANOVA) and multiple regression analysis. The findings revealed that: 1) The quality of working life, happiness at work and organizational engagement are high importance. 2) Different personal information have similar effects on organizational engagement. 3) Quality of working life in social relevance significantly affected organizational engagement at a statistical significant level of 0.01 and 4) Happiness at work love of work and work achievement significantly affected organizational engagement at a statistical significance level of 0.01 and recognition significantly affected organizational engagement at a statistical significance level of 0.05. The Suggestions of this study can be used as a guideline of developing the quality of working life and Creating happiness at work to make employees feel engaged with organization. The company should organize various internal and external activities for employees to participate comprehensively, emphasizing the value of every employee, providing opportunities for career advancement compensation and rewards to encourage employees in perform their work with quality.